Salmonella potsdam causing lumbar vertebral osteomyelitis: A case report. Issue 18 (May 2018) - Cheng, Weike; Lian, Kejian; Luo, Deqing; Lin, Dasheng; Feng, Wanqiang; Xian, Hang; Li, Tongtao
Abstract: Rationale: Salmonella osteomyelitis is an uncommon complication of salmonella infection, especially the salmonella vertebral osteomyelitis (SVO). Patient concerns: We reported a case of a 29-year-old female who presented with serious lower back pain and severe limitation of motion for 50 days with no obvious inducements. She once had a fever up to 39.5°C. Physical examination only revealed limited motion of lower back without neurological complications. The laboratory results revealed no specificity. MRI of the lumbar spine revealed a spondylodiscitis at L4-L5. She underwent anterior lateral approach debridement and percutaneous posterior instrumentation. Diagnoses: Tissue and abscess culture grew showed Salmonella Potsdam infection. Interventions: With susceptibility testing guidance, the patient was treated with intravenous levofloxacin and ceftazidime for a period of 3 weeks and another 3-week oral antibiotics therapy. Outcomes: The patient recovered well with no neurological deficits during the follow-up time. Lessons: SVO is really rare and it alerts us the importance to consider uncommon pathogens in the differential diagnosis in which the etiological evidences are crucial of healthy individuals.